Implementasi Etika Manajemen Sumber Daya Manusia di Lembaga Pendidikan Mas Al-Washliyah 22 Tembung - Syafri Fadillah Marpaung; Marsyela Marsyela; Marsyeli Marsyeli; Uswatun Hasanah (Journal of Islamic Economics and Finance, 2024)
This research aims to analyze the implementation of human resource management ethics at the MAS Al-Washliyah 22 Tembung Educational Institution. The method used is qualitative descriptive data analysis with a case study approach through interviews, documentation, observation with one of the teachers at MAS Al-Washliyah 22 Tembung. The aim of this research is to determine the implementation of human resource management ethics at the MAS Al-Washliyah 22 Tembung Educational Institution. This research will focus on the definition of educational ethics, human resource management such as the performance of employees or teaching staff and the productivity of teaching staff and the work morale of teaching staff. The research results show that ethics in human resource management principles must match the commitment of words with the achievement of personal performance through actions or work implementation. Which can build and create results from performance that are in line with common goals.